In silico docking reveals possible Riluzole binding sites on Nav1.6 sodium channel: Implications for amyotrophic lateral sclerosis therapy - Sierra Bello, Omar (2012)
Amyotrophic lateral sclerosis (ALS) is a common neurodegenerative disorder characterized mainly by a progressive loss of motor neurons. Glutamate excitotoxicity is likely the main cause of neuronal death, and Riluzole interferes with glutamate-mediated transmission. Thus, in such independent pathway, these effects may be partly due to inactivation of voltage-dependent sodium channels. Here we predict the structural model of the interaction and report the possible binding sites of Riluzole on Nav1.6 channel. The docked complexes were subjected to minimization and we further investigated the key interacting residues, binding free energies, pairing bridge determination, folding pattern, hydrogen bounding formation, hydrophobic contacts and flexibilities. Our results demonstrate that Riluzole interacts with the Nav1.6 channel, more specifically in the key residues TYR 1787, LEU 1843 and GLN 1799, suggesting possible cellular implications driven by these amino acids on Riluzole-Nav1.6 interaction, which may serve as an important output for a more specific and experimental drug design therapy against ALS. © 2012 Elsevier Ltd.